A non-fluorine method for preparing multifunctional robust superhydrophobic coating with applications in photocatalysis, flame retardance, and oil–water separation. (30th April 2019) - Wang, Bo; Peng, Shan; Wang, Yingchun; Li, Xinxin; Zhang, Kunmeng; Liu, Caiyun
Abstract : A PDMS-grafted method was proposed to fabricate robust PDMS-grafted-Mg(OH)2 /PDMS-grafted-TiO2 @epoxy coatings with multifunctional properties and various promising applications. Abstract : Superhydrophobic coatings (SHCs) have extremely promising, valuable, and practical applications in various indoor and outdoor scopes. However, many artificial SHCs still suffer from some problems such as the requirement of toxic and expensive reagents, weak mechanical durability or chemical stability, and complicated fabrication steps. In order to cope with the versatile, complex, and severe environment issues, developing multifunctional SHCs has become the main focus of researchers in recent years. In this study, we designed and fabricated a SHC composed of PDMS-grafted-Mg(OH)2 (PDMS-MH), PDMS-grafted-TiO2 (PDMS-TiO2 ), and epoxy. The original hydrophilic MH and TiO2 particles were covalently grafted with PDMS through heating and UV illumination method, respectively. The final coatings presented omnipotent properties. The coated fabric showed superior mechanical durability and chemically stable superhydrophobicity, which could withstand recycled abrasion treatment under a 200 g load at least 55 times. More importantly, it also achieved more protective abilities such as self-cleaning, anti-fouling, extremely stable underoil superhydrophobicity, photocatalysis, and self-quenched flame retardance. Moreover, the coated stainless steel mesh could not only highly efficiently separate oil–water mixtures under room temperature but also separate strongly acid/strongly alkaline/hot water–oil mixtures. Thus, it is believed that this multifunctional SHC not only fulfills real-life requirements but also has various highly potential applications in many fields.